Vasopora ceramica n. gen., n. sp.—a new abyssal cyclostome bryozoan from polymetallic nodules in the Russian exploration area, Clarion–Clipperton Fracture Zone, eastern Pacific Ocean - Grischenko, Andrei V.; Gordon, Dennis P.; Melnik, Viacheslav P. (Zootaxa, 2021)
A new abyssal cyclostome bryozoan genus and species, Vasopora ceramica n. gen., n. sp., is described from the eastern Russian exploration area of the Clarion–Clipperton Fracture Zone based on newly collected material from Yuzhmorgeologiya GLD4–19 station 421 (13.23408° N, 134.22180° W, 4809 m depth). Generic characters include an erect pedunculate colony with a distinct boundary between column and flared capitulum, short autozooidal peristomes in a single whorl, numerous alveoli, a central unidirectional sac-like gonozooid covered by a surficial network of crossed ridges continuous with adjacent rims of alveoli, a laterally opening ooeciopore, and the entire capitulum surface being minutely densely granular to subspinulate. Whereas the skeletal microstructure of the capitulum surface comprises irregular imbricated crystallites, the column has a planar-spherulitic fabric of acicular crystallites in fan-like arrays, and there are no pseudopores. The sharp boundary between capitulum and column, with their different microstructure separates Vasopora n. gen. from the two existing genera of Alyonushkidae that are found in the same environment. Vasopora n. gen. has a stalk formed of calcified exterior wall, whereas it is interior-walled in Alyonushka and Calyssopora.